Mythos und Tabula rasa: Narrationen und Denkformen der totalen Auslöschung und des absoluten Neuanfangs - Bizeul, Yves; Wodianka, Stephanie (Lettre, 2018)
Deconstruction and obliteration - mythical narratives of foundations from an interdisciplinary perspective.